Avaliação das ocorrências de larvas de Hypophthalmus edentatus e suas relações com o zooplâncton em uma lagoa marginal isolada na planície de inundação do Alto Rio Paraná - Mendonça, Marcos Marques (2012)
The lagoons are important lentic systems considered breeding and food sites for the growth stages of development of many fish species. The interrelationships among these communities in lentic marginal environments present as a complex dynamic that may be considered in determining structure, especially in terms of distribution and abundance of organisms in these communities. Among these interrelationships, the predator-prey interaction between organisms and zooplankton zooplanktivorous is one of the most important aspects in ecology. This study aimed to verify the occurrence of larval H. edentatus and relate the densities of zooplankton groups (cladocerans rotifers and copepods), specifically aims to: i) analyze monthly occurrences per period (day and night) and strata (surface and bottom) larvae of H. edentatus and zooplankton, ii) Relate the abundances of zooplankton with the larvae and iii) Relate the abundances of zooplankton with different stages of larval development. Samples were collected from October 2010 to March 2011 in the Xambrê lagoon in surface and bottom layers of the pond, at times 04h, 08h, 16h and 20h. Was registered the highest density of larvae in November and stage of development with higher density was flexion, being registered largest catches of larvae in the deep pond. Among the groups of zooplankton rotifers had higher abundance and positive relationship with the occurrence of larvae stage of pre-bending. According to the results, we can observe a sharp vertical migration behavior for larvae of H. edentatus especially for the later stages of development, which already possess greater swimming capacity. The opposite trends recorded (especially in January) indicate a possible larval predation pressure on zooplankton, especially the less advanced stages of rotifers and most advanced on cladocerans and copepods.